Factors influencing performance of nurses in the Makhuduthamaga Sub-District, Sekhukhune District, Limpopo Province, South Africa - Makunyane, Coshiwe Matildah (My University, 2012)
The purpose of the research was to explore the factors that affect the performance of nurses in the Makhuduthamaga Sub-district. The Research Design was quantitative descriptive. The population consisted of all categories of nurses working in the eighteen clinics of the Makhuduthamaga Sub-district that render a 24-hour service, seven days a week. The Stratified Random sampling technique was used to obtain the sample. Data were collected by means of designed performance instrument questionnaires. The study revealed that nurses were dissatisfied with their work, something that had a tremendous influence on their performance.
Thesis (MPH.) --University of Limpopo, 2012
Keywords: Performance; Nurses; Clinics; Primary health care; Nurses; Employees -- Rating of; Performance standards